Design of Tooth Profile of Cycloid Cam Outer Generator Swinging Teeth Drive - Yi Yali; Dou Linrui; Jin Herong; Zhang Wenchao (Jixie chuandong)
In order to realize the outer generator swinging rod teeth drive steadily transmit with high transmission ratio and heavy load,the cycloid curve with a continuous derivative curve till third order and the character of no rigid or no flexible impact is adopted as the tooth profile of outer generator cam. The plural-rectangular coordinate system is established,the outer generator cam teeth profile is designed with the method of plural vector,then the theory and the actual teeth profile equations of center gear are derived based on speed conversion principle and envelop theory. Through analyzing the curvature radius of center gear,the design conditions of avoiding interference of teeth profile is determined. The change law of transmission pressure angle is analyzed.